Multimodal discourse analysis : systemic-functional perspectives - O'Halloran, Kay L. (Open linguistics series., 2004)
This book brings together cutting-edge research on multimodal texts and the "discourses" generated through the interaction of two or more modes of communication, for example pictures of language, typography and layout, body movement and camera movement. The contributors collected within this volume use systemic functional linguistics to analyze how meaning is generated within a series of case studies. The result is a comprehensive survey of the ways in which enhanced meaning emerges through the interaction of more than one mode of communication. Multimodal Discourse Analysis will be useful to